Methodological aspects of Outpatient care module program - O. M. Drapkina; S. Yu. Astanina; D. I. Abdulganieva; I. G. Bakulin; I. A. Viktorova; L. Yu. Drozdova; A. V. Kontsevaya; O. Yu. Kuznetsova; M. A. Livzan; O. V. Khodakova; A. I. Chesnikova; N. L. Shaporova; et al. (Кардиоваскулярная терапия и профилактика)
.